Performance of additively manufactured kagome unit cells and its sandwich structures - Gautam, Rinoj (2019)
Lightweight, high strength and high energy absorption material are of interest in aerospace, automobile and defence industries. Sandwich structures with lattice core exhibit high specific strength and stiffness when compared to monolithic structures. The development of different additive manufacturing technologies has enabled the fabrication of complex cellular structures of low relative density, to enable energy management in impact and crash scenarios. It is necessary to investigate and enhance the mechanical properties of the lattice structure fabricated by additive manufacturing. In this thesis, quasi-static compression and flexural behaviour of Kagome sandwich structure fabricated by additive manufacturing is investigated. Fused deposition modelling (FDM) is useful to fabricate various parts of unmanned aerial vehicles (UAV). The structural efficiency of the UAV can be improved by using the cellular lattice structures which provides better specific strength and stiff structures. Thus, it is important to investigate the mechanical properties of the cellular structures fabricated by FDM. Initially, the compressive performance of Kagome unit cell structure of acrylonitrile butadiene styrene (ABS) fabricated by FDM is investigated. The influence of part build orientation, strut diameter and surface roughness on the strength and effective moduli is critically explored. The change in the build orientation improved the average peak strength and effective moduli by 23% and 19% respectively due to the change in strut dimensions with different build orientation as well as the anisotropic compressive behaviour of FDM printed parts. The finite element based numerical simulation results of effective stiffness differed from experimental measurements by 10-17% due to imperfections like voids and surface staircases which are imminent in the parts fabricated by FDM. The surface roughness of the printed parts was reduced by chemical surface treatment with 90% by vol. acetone. Five minutes treatment time on the Kagome specimens proved to be optimal based on the measured surface roughness, compressive strength and effective moduli of Kagome structures. Then, the compressive performance of unit Kagome structure was compared with the multi-units Kagome structures. The effect of the increase in the number of layers in the compressive performance in terms of average strength and effective moduli was also investigated. Also, the performance of uniform density and gradient density Kagome structure and their deformation behaviour were explored. It was found that the performance of the unit structure and multi-unit structure were comparable. The initial failure in both cases was similar and was around the joint of struts with the face sheets. The increase in the number of layers increased the effective moduli of the structure whereas the strength was almost the same within the relative density range of samples tested. The graded density Kagome lattice structure was found to have better energy absorption over the uniform density structures by 35%. Another major contribution of the thesis work is in the design modification of the existing Kagome structure to enhance the compressive performance. A vertical strut was introduced in the existing design and called as strut-reinforced Kagome (SRK) structure. The unit SRK and Kagome structure were successfully fabricated through selective laser melting without any additional support structure. The compression properties of SLM printed Ti-6Al-4V SRK was explored with the variation in the aspect ratio. An analytical prediction for effective modulus and peak strength of SRK structure was proposed and compared with numerical simulation and experimental results. The performance of unit SRK was also compared with unit Kagome structure with the same relative density. The analytical solution well predicted the compressive strength within 12% accuracy with the experimental results whereas the effective moduli differed by 12-24%. For the specific case studied, it was observed that the SRK unit structure had better effective modulus (12.87%) and peak strength (13.42%) than Kagome unit structure. The sub-β-transus heat treatment was carried out on SRK and Kagome samples, and they were subjected to compression tests. The peak strength of the structure reduced by 11-15% while the effective moduli of the structures increased by 40-48% after the heat treatment. The failure strain and energy absorption increased by 37-70% and 19-35% respectively with the heat treatment. Finally, the flexural performance of the sandwich beam with Kagome structure as a core was studied through finite element based numerical simulations. The analytical solutions for different failure modes under three-point bending were derived. A failure mode design map was constructed with non-dimensional failure loads expressed in terms of non-dimensional geometrical parameters of face sheet thickness and core height. Four different cases of various geometrical parameters were studied under three-point bending simulations in ABAQUS®, and the peak load, stiffness and failure mode were observed. The failure mode of the samples matched with the one predicted by failure map for core shear mode A and B and local indentation. The peak loads were found to be within 10% of the solution obtained by the analytical solution.